5-HT3 receptor antagonists protect against pressure overload-induced cardiac hypertrophy in murine - Rong Huo; Chang Chen; Yan Chen; Zhe Li; Yunlong Hou; Deli Dong (Elsevier, 2012)
Activation of cardiac sympathetic afferent reflex results in the increase of sympathetic activity. Serotonin (5-HT) activates cardiac sympathetic afferent through stimulating 5-HT3 receptors, the aim of present study is to test whether 5-HT3 receptor antagonists protect against cardiac hypertrophy. Cardiac hypertrophy induced by TAC for 4 weeks in mice was significantly inhibited by administration of 5-HT3 receptor antagonists, ondansetron (2.5 mg/kg, ip.) or tropisetron (2.5 mg/kg, ip.). Histological analysis revealed that the increased cardiac fibrosis in hypertrophic heart was relieved by ondansetron or tropisetron treatment. Ondansetron or tropisetron reduced the elevated plasma level of noradrenalin in mice with cardiac hypertrophy. Ondansetron and tropisetron had no effect on cardiomyocte hypertrophy induced by phenylephrine treatment in vitro. Finally, we took tropisetron as the representative drug and examined the effects of tropisetron on the desensitization of cardiac β-adrenergic receptor in rat treated with abdominal aortic banding (AB). Results showed that tropisetron restored the desensitization of cardiac β-adrenergic receptor in AB-treated rats. In conclusion, 5-HT3 receptor antagonists protected against cardiac hypertrophy and restored the desensitization of cardiac adrenergic responsiveness, the mechanism in which may be through reducing the sympathetic activity.